Efektivitas Batas Usia Penerimaan Peserta Didik Baru Terhadap Performa Belajar Mata Pelajaran PAI Di MIN 1 Bolaang Mongondow - Ramadhani, Aulia; Yahiji, Kasim; Matara, Kusmawaty (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study was conducted to reveal the effectiveness of the age limit for accepting new students on the learning performance of Islamic Religious Education (PAI) subjects at MIN 1 Bolaang Mongondow. This study was conducted using a qualitative descriptive approach and involved teachers and students as informants. The results showed that the age limit for accepting new students had a significant effect on learning performance. Students who enter school at the age of 7, in accordance with the regulations, tend to have better cognitive and emotional maturity, enabling them to follow lessons more effectively. Conversely, students who enter school before the age of 7 often face learning difficulties and require additional support. The study also identified differences in academic performance between students admitted within the age limit and those admitted outside the age limit. Older students (7 years old) demonstrate better readiness for learning, while younger students tend to have lower cognitive levels and require more support in the learning process. Based on the results of this study, the author recommends that teachers, parents, and students improve the quality of teaching and learning by adapting teaching methods, providing extra support for younger students, and fostering self-confidence and independence in students.